integrate 1/(e^xsquareroot1-e^-2x)dx how i started it: u= 1-1/e^2x du= -2e^-2xdx integrate dx/[(-u +1)u^1/2] dont know how to integrate the above
Follow Math Help Forum on Facebook and Google+
Originally Posted by twilightstr integrate 1/(e^xsquareroot1-e^-2x)dx how i started it: u= 1-1/e^2x du= -2e^-2xdx integrate dx/[(-u +1)u^1/2] dont know how to integrate the above i assume you mean note that this is the same as now, a substitution of yields the integral i suppose you can take it from here. i leave it to you to fill in the steps i omitted
View Tag Cloud